Heat Transfer and Heat Recovery Systems - Danielewicz, Jan; Rajski, Krzysztof (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Heat transfer plays a crucial role in modern engineering and energy conversion efficiency. Understanding its mechanisms is essential for sustainable energy management. Waste heat recovery, an increasingly popular strategy, reduces energy consumption and promotes sustainability. This reprint highlights advancements in heat transfer technology and heat recovery systems, addressing the persistent demand for innovative solutions. The content focuses on four main categories: heat transfer and heat exchangers, heat recovery, renewables, and domestic hot water preparation systems.